2012
DOI: 10.1016/j.juro.2012.04.118
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Laparoscopic Reoperative Repair for Failed Pyeloplasty in Children: A Safe and Highly Effective Treatment Option

Abstract: Robot-assisted laparoscopic reoperative repair of persistent/recurrent ureteropelvic junction obstruction is a safe, highly effective procedure even in the setting of multiple prior procedures. In our series all patients improved symptomatically, 88% improved radiographically and none have required further surgical intervention. Success is greater than with endopyelotomy and comparable to open reoperative repair for this challenging condition during short-term and intermediate followup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 22 publications
(33 reference statements)
1
28
0
Order By: Relevance
“…14 However, these results are not always similar to those obtained with LP by experts. 4,5,13 In our experience similar results can be obtained, and although both techniques have a long learning curve, PE takes less operative time.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…14 However, these results are not always similar to those obtained with LP by experts. 4,5,13 In our experience similar results can be obtained, and although both techniques have a long learning curve, PE takes less operative time.…”
Section: Discussionsupporting
confidence: 78%
“…3 Other treatments such as laparoscopic and robot-assisted laparoscopic pyeloplasty have displayed good results. 4,5 Primary endopyelotomy is known to be significantly less effective than open pyeloplasty and laparoscopic pyeloplasty in adults. 6,7 Following failed pyeloplasty secondary endopyelotomy has demonstrated results comparable to those of redo pyeloplasty in children.…”
mentioning
confidence: 99%
“…They concluded that redo RALP enables complex repairs in patients with previous failed repairs for UPJO and provides similar results to open surgery [24]. Lindgren et al [4] performed redo RALP in 16 pediatric patients with a success rate of 88%.…”
Section: Discussionmentioning
confidence: 97%
“…Dismembered pyeloplasty as first described by Anderson and Hynes is still the treatment of choice for UPJO with success rates over 90% [1,3,4]. LP and RALP have demonstrated similar success rates with the advantage of lower postoperative pain, shorter hospital stay and better cosmetic results especially in older children [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The learning curve for robotic surgery is much shorter than for straight laparoscopic procedures, particularly when intracorporeal suturing is involved, adding to its appeal and growing use. With the growing enthusiasm for its use RAL has been applied in many other urological procedures, including ureteral reimplantation for vesicoureteral reflux.…”
mentioning
confidence: 99%